Pemberdayaan KWT Melati Bersemi melalui Program GERBANG SERU Berbasis Pengolahan Nanas dan Pemanfaatan Limbah di Desa Seragam Jaya - Yuli Andriyati; Sari Atul Hilaliyah; Ahmad Hasanudin; Heriyanto Heriyanto; Mahmudah Mahmudah; Mukhamad Ikhsanul Yaqin (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service program aims to empower the Women Farmers Group (KWT) Melati Bersemi in Seragam Jaya Village, Kotawaringin Timur, through pineapple processing innovation and agricultural waste utilization. The village faces low market prices for fresh pineapples and unmanaged waste from pineapple peels and cores, which cause environmental problems. The GERBANG SERU (Gerakan Bangun Sirkular Ekonomi Unggul) program focuses on two main aspects: production and marketing. The method employed includes participatory training, technical assistance, and the application of appropriate technology. The results show that KWT members successfully processed pineapples into value-added dried pineapple products and utilized waste for maggot cultivation. In addition, members gained skills in simple business management, financial recording, and digital marketing strategies. This program has enhanced the group’s skills, income, and independence, while fostering the development of a local resource-based circular economy ecosystem.